A methodology for building mobile computing applications. (7th September 2004) - Chen, Minder
There is a tremendous amount of interest in developing mobile enterprise computing applications, driven by recent advancements in mobile technologies and standards, as well as an increasing mobile workforce population. However, many enterprises are uncertain of the various options they may have due to the emerging nature of mobile computing technologies. Additionally, they are concerned about the integration of mobile technologies with existing IT infrastructure and applications. In this paper, we propose a methodology to help enterprises develop business strategies and architectures for mobile computing. A generic mobile technical infrastructure is presented to assist enterprises in evaluating and implementing mobile applications. Software standards that may have major impacts on mobile technical architectures and application development are discussed. Finally, the implications of the proposed methodology for mobile computing for practitioners and researchers are discussed in the conclusion.